2019
DOI: 10.1186/s13018-019-1417-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orthopaedic surgeons’ and interventional radiologists’ availability on the priority treatment sequence for hemodynamically unstable pelvic fractures: a survey of US Level I trauma centers

Abstract: Background: Most guidelines recommend both pelvic packing (PP) and angioembolization for hemodynamically unstable pelvic fractures, however their sequence varies. Some argue to use PP first because orthopaedic surgeons are more available than interventional radiologists; however, there is no data confirming this. Methods: This cross-sectional survey of 158 trauma medical directors at US Level I trauma centers collected the availability of orthopaedic surgeons and interventional radiologists, the number of orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Reportedly, the time to angioembolization is longer than the time to PPP, partly owing to the higher availability of orthopedic surgeons compared with that of interventional radiologists ( 7 , 12 , 33 ); furthermore, TAE may be delayed at night or on weekends based on reports of other catheter-based interventions ( 16 , 34 , 35 ). In our institution, interventional radiologists and the equipment required for TAE are available at all times.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, the time to angioembolization is longer than the time to PPP, partly owing to the higher availability of orthopedic surgeons compared with that of interventional radiologists ( 7 , 12 , 33 ); furthermore, TAE may be delayed at night or on weekends based on reports of other catheter-based interventions ( 16 , 34 , 35 ). In our institution, interventional radiologists and the equipment required for TAE are available at all times.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the time to angioembolization is longer than the time to PPP, which may be in part due to the high availability of orthopedic surgeons as compared to that of interventional radiologists [7,12,32], and TAE may be delayed at night or on weekends based on reports of other catheter-based interventions [16,33,34]. In our institution, interventional radiologists and the equipment required for TAE are available 24 h a day, 365 days a year.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the time to angioembolization is longer than the time to PPP, which may be in part due to the high availability of orthopedic surgeons as compared with that of interventional radiologists [7,12,32], and TAE may be delayed at night or on weekends based on reports of other catheter-based interventions [16,33,34]. In our institution, interventional radiologists and the equipment required for TAE are available 24 h a day, 365 days a year.…”
Section: Discussionmentioning
confidence: 99%